Learning through Microteaching Lesson Study in Teacher Preparation - Fernández, Maria L. (Action in teacher education, 2005)
Prospective secondary mathematics teachers lack images of "reformed" teaching that engages students in experimenting, analyzing, conjecturing, justifying, and making connections. The development and investigation of experiences fostering reform-oriented teaching are needed. This study investigated microteaching lesson study (MLS), an experience based on the successful Japanese lesson study. A qualitative analysis of various data sources was conducted, demonstrating the learning and perceptions of 36 prospective mathematics teachers engaged in MLS. Overall, the prospective teachers found the experience to be very beneficial. Beyond providing teaching experience, the MLS facilitated enhancement of their understanding of reform-oriented teaching and knowledge of subject matter through collaboration with peers and feedback from an instructor.